2015
DOI: 10.1111/1365-2745.12512
|View full text |Cite
|
Sign up to set email alerts
|

Test of biotic and abiotic correlates of latitudinal variation in defences in the perennial herb Ruellia nudiflora

Abstract: Summary Geographic variation in abiotic factors and species interactions is widespread and is hypothesized to generate concomitant patterns of species trait variation. For example, higher rates of herbivory at lower latitudes are thought to select for increased plant defences, although latitudinal variation in defences may also be influenced directly by abiotic factors and indirectly by predators and parasitoids reducing herbivore pressure. We measured defences of the herb Ruellia nudiflora among 30 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 72 publications
2
73
1
Order By: Relevance
“…However, although plant damage is influenced by many factors, including herbivore-and plant-related characteristics (Abdala-Roberts et al, 2016;Grubb, 1992), it is widely expected that higher herbivore richness would lead to higher herbivory due to the species complementarity effect or species identity effect (Salazar & Marquis, 2012). In accordance with this expectation, recent experimental or synthetic studies have shown that, concomitant with the increases in herbivore richness, the herbivore pressure also increases (e.g.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, although plant damage is influenced by many factors, including herbivore-and plant-related characteristics (Abdala-Roberts et al, 2016;Grubb, 1992), it is widely expected that higher herbivore richness would lead to higher herbivory due to the species complementarity effect or species identity effect (Salazar & Marquis, 2012). In accordance with this expectation, recent experimental or synthetic studies have shown that, concomitant with the increases in herbivore richness, the herbivore pressure also increases (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Geographical variation in species interactions is central to our understanding of large-scale patterns in species abundance, diversity and functional traits (Abdala-Roberts, Moreira, Rasmann, Parra-Tabla, & Mooney, 2016;Moeller et al, 2017). Traditional theories, such as the latitudinal herbivory defence hypothesis and the elevational herbivory defence hypothesis, are based on the prediction that biological interactions such as herbivory are stronger at lower latitudes and at lower elevations (Dobzhansky, 1950;Pellissier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An association between latitude and plant defense or herbivore load holds for many groups of plants [30, 31] although in some cases the correlation between defenses and latitude may be more reflective of underlying variation in abiotic factors rather than variation in biotic interactions[3234]. The generality of a latitudinal gradient in herbivory and plant defense has been called into question[35], and a recent analysis found that across taxa most resistance traits were either unrelated to latitude or were greater at higher latitudes[36].…”
Section: Introductionmentioning
confidence: 99%
“…However, systemic induced responses may still take place and are not accounted for using this procedure. Accordingly, measured levels of chemical defences presumably represented a combination of constitutive defences and an unknown level of systemic induction due to herbivory occurred over the growing season (Abdala‐Roberts, Moreira, et al., ). After collection, we oven‐dried leaves for 48 hr at 40°C, ground them with liquid nitrogen, and stored the samples for subsequent quantification of phenolic compounds.…”
Section: Methodsmentioning
confidence: 99%
“…We tested whether the effect of insularity on insect herbivory was mediated by climate and/or changes in plant defences by running “mechanistic” models with insularity and phylogeographic group as fixed factors, as well as climatic factors or leaf chemical defences as covariates (PROC GLM in SAS 9.4). We tested for effects of defences on herbivory rather than the inverse because our analyses indicated that plant defences were negatively correlated with leaf damage (see section ), suggesting that defences drove herbivory (see Abdala‐Roberts, Moreira, et al., ). Specifically, we ran separate models including either climatic variables (temperature and precipitation) or plant defences, because running a single model with both types of predictors would not permit to tease apart the relative influences of climate versus leaf traits underlying the effect of insularity on herbivory.…”
Section: Methodsmentioning
confidence: 99%